Organizational Commitment among the Top-Level College Basketball Players in Japan: Focused on Bases of Power and School Stages at High School and University - Shota Nakazawa; Yusuke Kuroda (CV. FOUNDAE, 2024)
This study examined the degree of organizational commitment, the content of bases of power, and the relationship between organizational commitment and bases of power of high school and university stages of elite university basketball players in Japan. One hundred sixty-six (166) university basketball players from the Kanto University Basketball Federation Men's Division 1 League took part in this study. They completed questionnaires about their high school and university coaches. For organizational commitment, affective commitment was significantly higher for the high school stage than the university stage (p less than 0.001). For bases of power, the university stage had significantly higher scores for expert power (p less than 0.001), while closeness-trust power and punishment power scores were significantly higher in the high school stage (p less than 0.001). For the high school stage, motivational power and for the university stage, motivational and expert powers showed as determinants of organizational commitment. In the relationship between organizational commitment and bases of power in the high school stage, it was noteworthy that no significant influence of expert power was confirmed. The results suggested that it is important for coaches to rely on motivational and expert powers to increase organizational commitment. To nurture players who want to contribute to a team, it was speculated that coaches should constantly have strong motivation for coaching and make efforts to maintain relationships with their targets so that their attitude is understood by players, and also not neglect daily information gathering, training, and interaction among coaches to maintain high expertise in coaching.